Assessing stakeholders benefits of a microgrid energy system in Iceland - Valgeir Páll Björnsson 1991- (2020)
Past years have shown that occurances such as extreme weather, war, terrorism, seismic activity, and other events have illustrated the lack of resilience the electrical power grid of nations can have and how vulnerable society can be when power grids go out for longer time. There are, further, many barriers which will need to be crossed as to ensure sufficient supply for the increasing demand for electricity around the world. However, an increasing penetration of distributed energy resources that provide electricity into the existing grid has in recent years been developing an interesting scenario for power generation. Example of these developments are, for instance, the solar and wind farms. It is clear that reliability and resilience of electrical supply has gained its importance in regards to modern living for instance, communication, foodsupply storage and medical device. When a electrical power grid goes out for a longer time, numerous things that play a crucial role to maintain society, security and the economy can get affected. Micro electrical grids with independent power sources and generators might come in handy in such situations. The main objective of this paper is to spaculate about the potential social and economic benefits by which microgrids may have in countries that can be defined as developed. Microgrids are currently used in many places within the developing world, but the question being asked in this paper is: Could electrical microgrids with independent source energy benefit users in more developed countries as crucial backup when the larger electrical system can not supply? The microgrid gains are importance due to its ability to provide secure and sustainable electricity as back up, either as a compensation for the main grid or as a sole electrical supply when the main grid fails. In other words, the microgrid can be used both as a supplementary electrical generation at peak hours and as a full back-up when the large grid is down or cut off. Such a function of a microgrid is often ...